2016
DOI: 10.5812/atr.33664
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Carbapenem-Resistant Pseudomonas aeruginosa Isolates Carrying blaIMP Among Burn Patients in Isfahan, Iran

Abstract: BackgroundMetallo-β-lactamase (MBL)-producing Pseudomonas aeruginosa is a significant pathogen in burn patients.ObjectivesThe aim of this study was to determine the prevalence of carbapenem-resistant P. aeruginosa isolates, including those resistant to imipenemase (IMP), in a burn unit in Isfahan, Iran.Patients and MethodsOne hundred and fifty P. aeruginosa isolates from burn patients were tested for antibiotic susceptibility by the disc diffusion method in accordance with CLSI guidelines. Production of MBL wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 18 publications
2
19
5
Order By: Relevance
“…1, The study by Radan M et al and Naqvi et al showed 89% and 81.8% resistance to ticarcillin-clavulanic acid which are less than that of our findings. 3,6 In our study, we found that the isolates showed maximum resistance to cefoperazone sulbactam (96.77%) followed by cefepime (93.54%) and ceftazidime (90.32%). In the study by Bhatt et al 77% showed resistant to ceftazidime and 65% showed resistance to cefepime.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…1, The study by Radan M et al and Naqvi et al showed 89% and 81.8% resistance to ticarcillin-clavulanic acid which are less than that of our findings. 3,6 In our study, we found that the isolates showed maximum resistance to cefoperazone sulbactam (96.77%) followed by cefepime (93.54%) and ceftazidime (90.32%). In the study by Bhatt et al 77% showed resistant to ceftazidime and 65% showed resistance to cefepime.…”
Section: Discussionmentioning
confidence: 57%
“…A similar pattern of resistance shown in the Radan M et al all the isolates show 96% resistant to imipenem and meropenem. 3 But less drug resistance is seen in the study done by Rostami S et al, 14 among all isolated P.aeruginosa, 78.5%, 46.7%, and 15% were imipenem, meropenem, and doripenem resistant, respectively. 13 Similarly it was found that 61% isolates were resistant to imipenem and 54% were resistant to meropenem by Bhatt P et al 1 Aztreonam a potent monocyclic ß-lactam with good in vitro activity against P.aeruginosa.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations